Long-Run Effects of Post-Kyoto Policies: Applying a Fully Dynamic CGE model with Heterogeneous Capital - Lucas Bretschger; Roger Ramer; Florentine Schwark (ETH Zurich, CER-ETH - Center of Economic Research, 2010)
The paper develops a new type of CGE model to predict the effects of carbon policies on consumption, welfare, and sectoral development in the long run. Growth is fully endogenous, based on increasing specialization in capital varieties, and speci c in each sector of the economy. The benchmark scenario is calculated based on the endogenous gains from specialization which carry over to policy simulation. Applying the model to the Swiss economy we nd that a carbon policy following the Copenhagen Accord entails a moderate but not negligible welfare loss compared to development without any negative e ects of climate change. Energy extensive as well as capital and knowledge intensive sectors pro t in the form of increased growth rates.
Keywords: Q54; C63; O41; Q43; Q56; 330; Carbon policy; CGE models; energy and endogenous growth; heterogeneous capital; Klimawandel; Treibhausgas-Emissionen; Internationale Umweltpolitik; Internationale Arbeitsteilung; Allgemeines Gleichgewicht; Mehrsektoren-Modell; Endogenes Wachstumsmodell; Schweiz